GAMELAN SOEPRA SEBAGAI REKONTEKSTUALISASI GAMELAN JAWA - Nugrahanstya Cahya Widyanta (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Gamelan Soepra is an adaptation of Javanese gamelan. The difference lies in the tuning system and the physical form of the gamelan foot which is made higher. This difference has shifted the contextual meaning of Javanese gamelan. This descriptive qualitative research collected the data from field observations. Javanese gamelan has its own philosophical meanings which contain noble values. For example, the cross-legged sitting position on the floor for Javanese gamelan player implies the meaning of modesty. Gamelan Soepra does not have such meaning because of the higher physical form of its foot. The Gamelan has its own philosophical meaning.